Clostridium vitabionis sp. nov., isolated from the large intestine of a mini-pig. Issue 3 (8th March 2021) - Shin, Yeseul; Paek, Jayoung; Kim, Hongik; Kook, Joong-Ki; Chang, Young Hyo
Abstract : An obligately anaerobic, Gram-stain-negative, spore-forming, short rod-shaped bacterium, designated strain YH- T4B42 T, was isolated from the large intestine of a mini-pig. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the isolate belongs to the genus Clostridium and is most closely related to Clostridium aminophilum KCTC 5424 T, Clostridium symbiosum KCTC 15329 T and Clostridium butyricum KCTC 1871 T, with 95.5, 92.4 and 83.0 % sequence similarity, respectively. The average nucleotide identity values for strain YH-T4B42 T and the closest related strains were lower than 72 %. The G+C content of the isolate was 55.8 mol%. The cell-wall peptidoglycan was A1γ type and contained meso -diaminopimelic acid. The predominant fatty acids were C16 : 0, C18 : 1 cis 9, C14 : 0 and C18 : 0 . The major end products of glucose fermentation were lactate, formate and acetate, with a minor amount of butyrate. Based on its phenotypic, phylogenetic and chemotaxonomic properties, a novel species, Clostridium vitabionis sp. nov., is proposed for strain YH-T4B42 T (=KCTC 25105 T =NBRC 114767 T ).